(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to defining the content of a special type of legal thinking – criminal-legal – from the standpoint of doctrine and academic discipline. The focus is on approaches to better teaching and teaching the first topic “Criminal Law as a Branch of Law, Science and Academic Discipline”. It reveals what is important for a better understanding and application of criminal law norms in practice and in general for the development of a broad worldview. We have analyzed the first topic as thoroughly as possible in about twenty textbooks, textbooks on criminal law. In this way, in the scientific article you can see the presentation of the material and the general position of many schools of criminal law in Ukraine.